Prey - Predator Relationship between the Asian Citrus Psyllid (Diaphorina Citri Kuwayama) and the Metallic Blue Ladybeetle (Curinus Coeruleus Mulsant - Soemargono, Albertus (2007)
The Asian citrus pyllid, Diaphorina citri Kuwayama is one of the citrus most notable pests of economic importance, owing not only to the direct damages caused but also indirect ones. It is the principal vector of the greening disease which is considered as the most serious disease of citrus in the world. It was noted that the greening disease has destroyed an overall estimate of 50 millions trees, most of this loss being accounted for by South and South East Asian countries in 1980’s. A survey conducted by the Department of Agriculture, Malaysia in 2001 showed that 52% of Citrus suhuensis cv. Limau madu grown in Peninsular Malaysia indicated positive symptom of the greening disease. To overcome this problem, pest control measures including biological control have been attempted. The metallic blue ladybird beetle, Curinus coeruleus Mulsant, one of the predaceous coccinellids, is known to reduce the population of D. citri.